CONTRIBUTION TO THE STUDY OF FLOCCULATION OF DIGESTATE - Heviánková, Silvie (GeoScience Engineering, 2015)
The paper deals with the intensification of separating the solid phase of digestate using flocculants only. The separated solid phase should subsequently be used in agriculture for fertilising. Flocculants (polyacrylamides), which are difficult to biodegrade, thus must not deteriorate the properties of the solid phase and the dose of the flocculant must be unobjectionable. The research aimed to identify the optimal cation-active flocculant and its application procedure which would enable dosage that would be both economically and ecologically acceptable. We tested 21 cation-active flocculants of different charge density and molecular weight with the aim to discover the lowest possible dose of flocculation agent to achieve the effective aggregation of digestate particles. The lowest flocculant doses were obtained using the mixture of flocculants labelled Sokofloc 53 and Sokofloc 54 in 4:1 proportion, both of a low charge density and medium molecular weight, namely 14.54 g/kg of TS (digestate from biogas station Stonava) and namely 11.80 g/kg of TS (digestate from biogas station Vrahovice). The findings also reveal that flocculation is most effective during two-stage flocculant dosing at different mixing time and intensity.